\(Bài2\\ a,3,8:\left(2x\right)=\dfrac{1}{4}:2\dfrac{2}{3}\\ =>\dfrac{19}{5}:2x=\dfrac{1}{4}:\dfrac{8}{3}\\ =>\dfrac{19}{5}:2x=\dfrac{3}{32}\\ =>2x=\dfrac{19}{5}:\dfrac{3}{32}\\ =>2x=\dfrac{608}{15}\\ =>x=\dfrac{608}{15}:2\\ =>x=\dfrac{304}{15}\)
\(b,\dfrac{\left(-2\right)^x}{16}=-8\\ =>\left(-2\right)^x=\left(-8\right).16\\ =>\left(-2\right)^x=-128\\ =>\left(-2\right)^x=\left(-2\right)^7\\ =>x=7\\ \)
\(c,\left(x+\dfrac{1}{2}\right)^2=\dfrac{1}{16}\\ =>\left[{}\begin{matrix}x+\dfrac{1}{2}=\dfrac{1}{4}\\x+\dfrac{1}{2}=-\dfrac{1}{4}\end{matrix}\right.\\ =>\left[{}\begin{matrix}x=\dfrac{1}{4}-\dfrac{1}{2}\\x=-\dfrac{1}{4}-\dfrac{1}{2}\end{matrix}\right.\\ =>\left[{}\begin{matrix}x=-\dfrac{1}{4}\\x=-\dfrac{3}{4}\end{matrix}\right.\)
\(d,\dfrac{1}{2}.2^x+4.2^x=9.2^5\\ =>2^x\left(\dfrac{1}{2}+4\right)=9.32\\ =>2^x.\dfrac{9}{2}=288\\ =>2x=288:\dfrac{9}{2}\\ =>2x=64\\ =>x=64:2\\ >x=32\)